Analysis of a direct access testing system for the detection of SARS-CoV-2 in the paediatric population attending school - Bert, F.; Lo Moro, G.; Barbero, S.; Boietti, E.; Minutiello, E.; Sinigaglia, T.; Fagioli, F.; Siliquini, R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. During the COVID-19 pandemic, the paediatric population plays a minor role in the spread of the SARS-CoV-2 virus. However, in order to keep schools open and reduce SARS-CoV spreading, it is necessary to identify and isolate early SARS-CoV-2 positive paediatric patients even if they are asymptomatic. The aim of this study was to describe a setting for SARS-CoV 2 testing based on the spontaneous presentation of paediatric patients attending school without a medical prescription and explore its appropriateness.Study design. Cross-sectional study.Methods. The study performed between September 2020 and March 2021 among a sample of 13,283 paediatric patients who underwent a swab in four different hospital settings (school hot spot, emergency department, day hospital setting and hospital wards). For each patients we collected: date of swab execution, type of swab, execution setting of the swab, result of the swab, information about community spread of the virus in the 14 days prior to the swab execution, sex and age.Results. In our sample, females accounted for 45.8%. The median age was 6.8 years (IQR 3.0-11.2) and the most frequent age category was between 6 and 11 years (27.9%).At multivariable models with a swab tested positive as outcome. The swabs executed in all the hospital settings had a lower likelihood of resulting positive compared with the school hot spot setting. Compared with adolescents aged between 14 and 19 years old, new-borns below 3 months (adjOR 1.83, 95% C.I. 1.14-3) and patients aged between 11 and 14 years old (adjOR 1.32, 95% C.I. 1.07-1.63) reported a higher probability of a swab tested positive. Instead, children aged between 3 months and 3 years (adjOR 0.77, 95% C.I. 0.61-0.96) and children aged between 3 years and 6 years (adjOR 0.66, 95% C.I. 0.53-0.83) were less likely to result positive. The higher was the mean of pooled Rt in the 14 days preceding the swab, the higher was the likelihood of resulting positive (adjOR 1.75, 95% C.I. 1.53-1.99).Conclusion. In conclusion, we found a high incidence of paediatric patients positive to the test for the detection of SARS-CoV-2 at the school hot spot compared with other settings during the period of observation. The free access modality to the nasopharyngeal swab was effective in identifying patients with COVID-19. Public health authorities should implement these testing modality in order to help reduce the spread of SARS-CoV-2 in school settings.